Exhumation and Surface Evolution of the Western High Atlas and Surrounding Regions as Constrained by Low‐Temperature Thermochronology - Lanari, R.; Fellin, M. G.; Faccenna, C.; Balestrieri, M. L.; Pazzaglia, F. J.; Youbi, N.; Maden, C. (Tectonics (Washington, D.C.), 2020)
The Moroccan High Atlas, the Anti‐Atlas belts, and the Siroua volcanic massif form an orographic system locally risen to elevations over 4 km. Topographic growth of this system occurred by Cenozoic transpressive inversion of Mesozoic rift structures concomitant with volcanic activity and related mantle processes. In order to constrain the topographic growth, we analyze the regional‐scale exhumation pattern, and we compare it to physiographic features. We contribute 35 new mean (U‐Th‐Sm)/He and 24 new fission track ages on apatite from the High Atlas and Anti‐Atlas, which all together range from 196 to 5 Ma. In the Anti‐Atlas, we find that the rate and amount of Cenozoic exhumation are <0.05 km/Ma and ~2 km, respectively. In the High Atlas, our new data together with previous ones show that the axial regions feature the highest topography, relief, channel steepness, and orographic precipitations together with the maximum rate and amount of Cenozoic exhumation, in the range of 0.2–0.3 km/Ma and 4–6 km, respectively. This region is bounded by high‐angle oblique‐slip faults, which display a Neogene vertical motion of a few kilometers. Moreover, the most deeply incised valley in the axial region of the High Atlas shows stepwise cooling and exhumation with a final acceleration after 6 Ma. We conclude that the location in the same region of high river channel steepness, topography, orographic precipitations, and rates and amount of exhumation, together with large vertical offsets along oblique‐slip faults, suggests that crustal deformation may exert a major control on the topographic growth of Atlas orographic swell. Key Points Cooling ages constraint the maximum amount of exhumation of 6 km in the axial regions and 4.4 km in the frontal regions of the western High Atlas Thermal modeling indicates a rapid cooling event at 10 Ma Morphometric and exhumation pattern indicate remarkable differences along the High Atlas